Smoking Prevalence Among Khulna University Students: Investigating Knowledge, Attitudes, and Contributing Factors - Turzo, Noor A Alam; Hassan, Sakib Al; Kabir, Falah-Un-Nesa; Al-Mahde, Abdul Elah; Jui, Mahmuda Akter; Anni, Tayeeba Tabussum; Islam, Tanjirul (Papanda Publisher, 2025)
Background: Smoking is still a significant global public health concern, especially for young people who are more likely to start and maintain smoking habits that could result in long-term health problems. The current study aims to measure smoking prevalence and attitudes among students and identify the associated factors of smoking. Methods: The quantitative method determined smoking prevalence, attitudes, and associated factors among students. A simple random sampling technique was used in the study area. 29 disciplines of the Khulna University campus were enrolled in this study. To observe the smoking initiation rates while studying at the university, first-year to master’s level students participated. Results: A total of 270 students were enrolled. Among them, almost 40.37% of respondents were non-smokers. To measure nicotine dependency, the Fagerstrom test was used. Compiled responses showed that the highest number of respondents, with a percentage of 24.07%, were found to have moderate nicotine dependence, with a score of 5-7. The second highest number of respondents (17.41%) was found to have low to moderate dependence on nicotine. The findings revealed that among the Knowledge and Attitude towards smoking, Students who oppose public smoking bans have a higher likelihood of nicotine dependence (AOR = 6.8, p < 0.001). The belief that smoking causes illness has no significant impact on nicotine dependence (AOR = 1.06, 95% CI: 0.47-2.40, p = 0.886) through a logistic regression model. Conclusion: Students older than 20 are more likely to smoke than those under 20. Family, social environment, and the smoking behavior of friends influence smoking. All risk factors, including history and university period, should be considered together in tobacco control.